Protocol for the evaluation of prosody and pragmatics in people with schizophrenia - Martínez, Alfonso; Martínez-Lorca, Manuela; Santos, Jose Luis; Martínez-Lorca, Alberto (Revista de Investigación en Logopedia, 2018)
Schizophrenia is characterized by a distortion of thinking, perceptions, emotions, language, self-awareness and behavior. It affects more than 21 million people worldwide and is one of the 10 most disabling diseases according to the World Health Organization, but there is little evidence of the language deficit entailed by the disease.This is a cross-sectional and quasi-experimental study. A battery of different assessment instruments was used to evaluate pragmatics and prosody in a sample of 96 subjects, of which 48 (50%) had no mental illness (control group) and 48 (50%) had mental illness (experimental group).According to the classification of Crow (1978), 56.7% of the subjects of the experimental group (27 subjects) showed positive symptomatology and 43.8% (21 subjects) showed negative symptoms. Different deficit patterns were observed according to the symptomatology, as well as impairment of the areas assessed in the present study (pragmatics and affective prosody). Schizophrenia entails a deficit in the analyzed areas, although there is a controversy about its origin. Concerning pragmatics, literal interpretations are to be found in both types of patients, but these are more frequent in subjects with positive symptomatology. As for prosody, the appearance of excessively high fundamental frequencies, monotony in the expression of emotions, and difficulties for the understanding of affective prosody are the most salient characteristics of all the patients in the experimental group.
Keywords: schizophrenia; language; assessment; pragmatics; affective prosody